Development of a dual RT-RPA detection for Sweet potato feathery mottle virus and Sweet potato chlorotic stuntvirus. (October 2022) - Tang, Wei; Yang, Dongjing; Ma, Jukui; Chen, Jingwei; Xie, Yiping; Sun, Houjun; Zhang, Chengling
Abstract: The disease co-infected by Sweet potato feathery mottle virus (SPFMV) and Sweet potato chlorotic stunt virus (SPCSV) is devastating in sweet potato, as it would give rise to the serious losses in both production and quality. Consequently, it is conducive for preventing and controlling this disease to detect these two viruses accurately and timely. Here we developed and optimized a dual reverse transcription recombinase polymerase amplification (RT-RPA) for rapid and accurate detection of SPFMV and SPCSV. Four special primers were designed based on the conserved sequences of SPFMV and SPCSV, respectively. The sensitivity of dual RT-RPA for SPFMV and SPCSV was 10 −4 ng/μL at the optimal conditions in which the primer ratio between SPFMV and SPCSV was 2:1, and the reaction incubated for 25 min at a temperature of 39 °C. Both 61 sweet potato samples and 5 morning glory samples collected from China were tested using the dual RT-RPA successfully. Therefore, the dual RT-RPA is a reliable, rapid, sensitive method to detect these two viruses in sweet potato. It is the RT-RPA that was used for detection of SPFMV and SPCSV simultaneously firstly. This dual RT-RPA, as a convenient and powerful tool, will be useful to diagnose SPFMV and SPCSV. Highlights: A highly sensitive RPA assay was developed for the detection of SPFMV and SPCSV simultaneously. . The dual RT-RPA assay can detect SPFMV and SPCSV in only 20 min. . The dual RT-RPA assay showed high consistency with RT-PCR. .